Assessing the Impacts of Queue Jump Lanes at a Signalized Intersection: A Case Study of Narayan Gopal Intersection - Aryal, Kiran; Shrestha, Pradeep Kumar; Khatiwada, Pragya (International Journal on Engineering Technology, 2024)
One of the main causes of congestion in Nepal’s urban areas is the preference for private transportation over public transportation. In other contexts, research on bus priority measures has demonstrated their potential to reduce transit delays, enhance bus reliability in mixed-traffic conditions, and optimize travel times. This study aims to assess the effectiveness of introducing queue jump lanes in an isolated signalized intersection of Kathmandu Valley, applying these concepts to Nepal’s heterogeneous traffic conditions. VISSIM microsimulation software was used to model the existing scenario and four different QJL configurations at the Maharajgunj intersection to assess the impacts on travel time and delay. Results reveal that adding a left-turn-only lane adjacent to a QJL with pre-signal can significantly save travel time and reduce delay at the Maharajgunj intersection.